Electroretinography in eight species of neotropical deer - Crivelaro, R. M. [UNESP]; Thiesen, R.; Aldrovani, M. [UNESP]; Lima, T. B. [UNESP]; Ortencio, K. P. [UNESP]; Padua, I. R. M. [UNESP]; Duarte, J. M. B.; Laus, J. L. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
The aim of this study was to establish normal baseline ERG values of 23 anesthetized deer belonging to 8 neotropical species (Mazama americana, Mazama nemorivaga, Mazama gouazoubira, Mazama nana, Mazama bororo, Ozotocerus bezoarticus, Odocoileus virginianus and Blastocerus dichotomus). Only right eyes were studied. Chemical restraint was performed using xylazine associated with ketamine, IM, for M. americana, M. gouazoubira, M. nemorivaga, M. nana, M. bororo, O. bezoarticus and O. virginianus. A combination of tiletamine/zolazepam diluted in xylazine 2% was used for B. dichotomus individuals. After 20min of dark adaptation, electroretinograms were obtained using a handheld electroretinography (ERG) machine using the QuickRetCheck Protocol at three different light intensities: 0.01cd.s/m(2), 3cd.s/m(2), and 10cd.s/m(2). After light adaptation, photopic phase was recorded. A-wave amplitude recorded during pattern mixed rod/cone response in M. americana was significantly lower when compared to B. dichotomus. No other differences were observed between the species studied. ERG in Neotropical deer is applicable using a portable ERG system and did not show differences among species in relation to the retinal response at different light intensities. Therefore, the lifestyle of the species is more dictated by the selection pressure of the environment than by physiological factors.
Keywords: cervidae; habitat; retina; wild animal; ERG